CARTA À RAINHA LOUCA: UMA LEITURA A PARTIR DA CRÍTICA FEMINISTA NA PERSPECTIVA DECOLONIAL - MARCIA GOMES DE LIMA (2023)
This work has been developed from reading “Carta à Rainha Louca – Letter to the Mad Queen” (2019), by Maria Valéria Rezende, a brazilian writer and feminist who revisits colonial Brazil to write an epistolary novel, whose main character is Isabel das Santas Virgens, a female voice who, through letters addressed to the Portuguese Crown in the figure of Queen Maria I, reports and denounces the conditions imposed on black people, indigenous individuals, and, above all, women. As our main focus, we recall that silence and subservience have always been the order for female bodies, because in our America (Central, South and Latin) and especially in Brazil, since the European arrival (or intrusion) to the present day, violence against these bodies has become a constant, and imposing oneself on them was the way to carry out and establish colonization. In this sense, this research proposes, based on the aforementioned work, a critical reading of the forms of (re)presentation of female bodies in the context of colonial Brazil, from a perspective of decolonial feminist studies. Therefore, the studies of Maria Lugones, (2019; 2020), Rita Laura Segato (2021), Julieta Paredes (2008), Anibal Quijano (2005), among others, were used as theoretical input. Keywords: Carta à Rainha Louca – Letter to the Mad Queen; Colonial Brazil; Coloniality of gender; Maria Valéria Rezende; Epistolary novel.